2019
DOI: 10.1016/j.gaitpost.2019.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of single-leg drop jump landing performance by means of ground reaction forces: A methodological study

Abstract: Background: Time to stabilization (TTS) and dynamic postural stability index (DPSI) are outcome measures based on ground reaction force (GRF) that are often used to quantify dynamic postural stability performance following a drop jump landing. However, their interrelations, as well as the overlap with other dynamic measures and static single-leg postural sway, are unknown. Research question: What is the relation among TTS and DPSI, how are they related to impact forces and dynamic postural sway, and how are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Single-leg body sway parameters can be used for analyzing the static performance of stabilization in the condition of unilateral distribution of body weight, which is usual in sports activities. Good single-leg stabilization characteristic reflects on the smaller increase in vertical force and the shorter weight transfer in different movement tasks [17,18]. The single-leg stance test is also recommended for clinicians as a useful tool for a brief assessment of the risk of falling [19].…”
Section: Introductionmentioning
confidence: 99%
“…Single-leg body sway parameters can be used for analyzing the static performance of stabilization in the condition of unilateral distribution of body weight, which is usual in sports activities. Good single-leg stabilization characteristic reflects on the smaller increase in vertical force and the shorter weight transfer in different movement tasks [17,18]. The single-leg stance test is also recommended for clinicians as a useful tool for a brief assessment of the risk of falling [19].…”
Section: Introductionmentioning
confidence: 99%
“…First, the DPSI did not correlate with the sum of the frame subtraction scores in any plane. The DPSI reflects the COM deceleration immediately after the jump landing, which indicates kinematic energy absorption [ 15 ]. In this study, the peaks of the frame subtraction scores were indicated immediately after single-leg jump landing.…”
Section: Discussionmentioning
confidence: 99%
“…The DPSI is indicated by the ground reaction force (GRF) that combines its components, such as the medial‒lateral stability index (MLSI), anterior‒posterior stability index (APSI), and vertical stability index (VSI). Since the DPSI is calculated by integrating the GRF components in three directions, it could comprehensively represent the ability to absorb the GRF in jump landing [ 15 ]. The DPSI is therefore a highly reliable and precise measure of dynamic postural stability [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, outcome measures based on these forces, cannot be calculated. Parameters calculated from horizontal forces, such as TTS and absolute average forces, could provide relevant information on postural stability [ 47 , 48 ]. Another limitation of this study was the limited sample size (n = 42), although this was larger than in a recent study assessing reliability of drop landing [ 44 ].…”
Section: Discussionmentioning
confidence: 99%